Management of Type 2 Diabetes Mellitus Cases with Diabetic Neuropathy Complication and Hypertension Grade II through the Approach of Family Medicine - Normalisa Aulia; Ernawati Ernawati (Institute of Computer Science (IOCS), 2022)
Family medicine is an academic and clinical discipline focused on providing sustainable, comprehensive, coordinated and contextual primary health care for individuals, families, and communities. Diabetes Mellitus (DM) is a chronic metabolic disorder accompanied by disturbances in carbohydrate, fat, and protein metabolism due to reduced insulin function. Based on the IDF, it is estimated that there are 537 million people in the world suffering from DM in 2021 with 19.5 million people coming from Indonesia. In 2018, there were 23,262 cases found in Banten province. DM is the 3rd most common disease in the world. Mrs. E is one of the patients suffering from diabetes mellitus with hypertension and diabetic neuropathy Controlled blood sugar levels and blood pressure in Mrs. E aimed to there are no worsening complications of diabetic neuropathy and prevent other complications. A female patient, 49 years old, came to the Kresek Health Center to take part in Prolanis activities, the patient claimed to have a history of DM for the last 3 years. Currently the patient feels tingling in both legs since about 2 weeks ago. Complaints of tingling come and go and the last 3 days the complaints were increasingly felt. The problem analysis was carried out with a family medicine approach using the Mandala of Health so that a holistic diagnosis was obtained for comprehensive management. After the intervention, there was clinical improvement, GDS decreased from 325 mg/dL to 260 mg/dL and blood pressure decreased from 150/80 mmHg to 130/80 mmHg. The risk factors, internal and external factors cause the disease in Mrs. E and the findings of comprehensive management and the results of its management.